Research and design of test platform for rack drive system - SHANG Qin; LIU Dewei; CHEN Qingjian; BAI Yongping; QIAN Jifu; MENG Yuanwen (机车电传动)
In recent years, mountainous rack railways have emerged in China. Rack trains operating on these railways showcase exceptional climbing capabilities on slopes with a maximum slope of 250‰ ~ 480‰, which is more than 10 times the capacity of ordinary railway trains. The core components of rack trains are the rack bogie and rack drive device, whose performance and reliability are directly related to the successful development and operational safety of these trains. Therefore, conducting bench tests before assembly on trains is essential to fully verify their functional availability, quality reliability, and operational safety. Given the lack of suitable test benches in China for such research, this paper aims to establish a test and verification platform for rack drive systems, taking into account their characteristics and functional requirements. Following an introduction to the main functions, principles, and structures of the rack drive system test platform, this paper describes the overall architecture and various systems, including mechanical, hydraulic, electrical, testing, control, and monitoring systems. The main characteristics and technological innovations of the test platform are summarized, followed by an explanation of its application. The successful establishment and application of the rack drive system test bench have filled the gap in China, thereby enhancing the testing methods for drive systems in rack trains. This advancement marks the availability of necessary experimental research conditions for the development of rack drive systems in China and facilitates the rapid iterative development of core technologies for rack trains.